Data on megakaryocytes in the bone marrow of mice exposed to formaldehyde - Zhang, Yuchao (Data Brief, 2016)
Previously, we reported that occupational exposure to formaldehyde (FA) exposure in factory workers reduced platelet counts, http://dx.doi.org/10.1158/1055-9965.EPI-09-0762[1], while exposure in mice increased platelet counts http://dx.doi.org/10.1371/journal.pone.0074974[2]. Bone marrow megakaryocyte (MK) numbers were also increased in exposed mice, as determined qualitatively. The data presented here are from a quantitative evaluation of MK numbers in the bone marrow histopathological slides from the previous FA exposure experiments in mice. Bone marrow slides were prepared using a single 5 μm section of femur from 2 mice randomly selected from each exposure group (n=9) treated with 0, 0.5 and 3.0 mg/m(3) FA by nose-only inhalation. MKs were systemically counted and average MK frequency was calculated as the total MK per slide divided by the number of fields evaluated. Data are presented visually as microscopy views and graphically as MK frequency.